2021
DOI: 10.1161/circresaha.120.318364
|View full text |Cite
|
Sign up to set email alerts
|

A Neuroligin Isoform Translated by circNlgn Contributes to Cardiac Remodeling

Abstract: Rationale: Fibrotic cardiac remodeling is a maladaptive response to acute or chronic injury that leads to arrythmia and progressive heart failure. The underlying mechanisms remain unclear. Objective: We performed high-throughput RNA sequencing to analyze circular RNA (circRNA) profile in human cardiac disease and developed transgenic mice to explore the roles of circNlgn. Methods and Results: Using RNA seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Our previous study showed that expression of circNlgn induced cardiac fibrosis. 38 We examined the effect of doxorubicin on cardiac fibrosis by Masson’s trichrome staining and Sirius red staining. While we confirmed promotion of Masson’s trichrome and Sirius red staining in the circNlgn-transgenic mouse heart relative to the wild-type mouse heart, we detected an additive effect of doxorubicin treatment on both types of staining ( Figure 1 F), suggesting the promotion of cardiac fibrosis by doxorubicin treatment in the circNlgn-transgenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study showed that expression of circNlgn induced cardiac fibrosis. 38 We examined the effect of doxorubicin on cardiac fibrosis by Masson’s trichrome staining and Sirius red staining. While we confirmed promotion of Masson’s trichrome and Sirius red staining in the circNlgn-transgenic mouse heart relative to the wild-type mouse heart, we detected an additive effect of doxorubicin treatment on both types of staining ( Figure 1 F), suggesting the promotion of cardiac fibrosis by doxorubicin treatment in the circNlgn-transgenic mice.…”
Section: Resultsmentioning
confidence: 99%
“…circRNA_000203 exacerbates cardiac hypertrophy by inhibiting miRNA expression ( Li H. et al, 2020 ). Meanwhile, circNlgn was translated to neuroligin and found to promote remodeling in pressure overload hearts ( Du et al, 2021 ). Furthermore, Tijsen et al (2021) first reported that the contractile protein titin formed circRNAs (cTTN1) transcript is important for the splicing of several muscle genes including titin itself.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, non-coding circular RNAs (circRNAs) were reported to regulate heart failure progression ( Li et al, 2018 ; Zhang et al, 2020 ). These non-coding RNA molecules are transcript isoforms that occur as covalently closed continuous loops that act as miRNA sponges, interact with RNA binding proteins, or are translated into proteins, exerting a broad range of effects on the heart ( Altesha et al, 2019 ; Kristensen et al, 2019 ; Du et al, 2021 ). The most investigated function of circRNAs is miRNA sponging in which circRNAs and mRNAs competitively bind miRNAs to regulate gene expression, which is designated ceRNA regulation ( Salmena et al, 2011 ; Hansen et al, 2013 ; Thomson and Dinger, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Circular transcripts, first discovered in 1976 in a plant viroid, attracted little attention at the time and were treated as abnormal by-products or "splice noise" with low abundance and low functional potential [33][34][35][36]. Due to the development of high-throughput screening technology, more types of circRNAs have been identified in a variety of species and cell lines [22,[37][38][39][40]. The expression level of circRNAs is relatively rich and highly conserved.…”
Section: Overview Of Circrnas 21 Biogenesis and Classification Of Circrnasmentioning
confidence: 99%